The influence of ESG dimensions on financial performance: evidence from Egyptian listed firms - Mahboub, Rasha; Ghanem, Mohamed (Frontiers in Sustainability, 2025)
IntroductionEnvironmental, Social, and Governance (ESG) dimensions have transitioned from being a specialized concern to a fundamental aspect influencing a company’s financial performance (FP). As stakeholders increasingly emphasize sustainability, organizations are compelled to integrate ESG considerations into their strategic frameworks. This study aims to investigate the role of ESG dimensions in driving the FP of publicly listed companies on the Egyptian Stock Exchange (EGX) from 2018 to 2022.MethodsData was gathered from the top 100 Egyptian firms rated by liquidity and activity using a quantitative research methodology covering 14 different industrial sectors. The analysis utilized financial statements, annual reports, sustainability reports, and corporate governance documents.ResultsIt was found that the environmental dimension does not significantly influence FP, while the social dimension has a negative and significant effect. Additionally, the findings reveal a positive influence of the governance dimension on FP.Discussion and conclusionsThese results underscore the complex nature of ESG’s impact on a firm’s financial outcomes, emphasizing the necessity of examining specific ESG components. The insights derived from this study are valuable for stakeholders, including investors and policymakers, as they navigate the relationship between ESG dimensions and FP.